Informality and mobility. Issue 2 (April 2015) - Slonimczyk, Fabián; Gimpelson, Vladimir
Abstract Informality is a defining characteristic of labour markets in developing and transition countries. This paper analyzes patterns of mobility across different forms of formal and informal employment in Russia. Using the Russian Longitudinal Monitoring Survey household panel we estimate a dynamic multinomial logit model with individual heterogeneity and correct for the initial conditions problem. Simulations show that structural state dependence is weak and that transition rates from informal to formal employment are not lower than from non‐employment. These results lend support to the integrated view of the labour market.